ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CUSTOMER SATISFACTION PADA RESTORAN-RESTORAN DI SURABAYA - Erna Susanti (Perpustakaan Universitas Surabaya, 2014)
The purpose of this study is to analyze and measure the factors and the factors that influence customer satisfaction in service based food service restaurants in Surabaya evaluation factors. From the research conducted, its howed that the factors that affect overall customer satisfaction on service restaurants in Surabaya is the price and value and of a number of a sample of respondents in this study formed a cluster that value seekers. The factors that affect customer satisfaction on service restaurants in Surabaya on value seeker sare menu diversity and noise.